PERMUKIMAN BARU HEMAT ENERGI DI SUDIROPRAJAN - Rychell Lyaputera; Budi A. Sukada (Jurusan Arsitektur dan Perencanaan, 2021)
Basically, the present human being lives their life by the support of nature and other beings to maintain ecological balance. The problems that the world is facing today, among others, is that it has become imbalance due to the increasing numbers of people when the stock of land and food resources are decreasing. One of the result of such imbalance is the increasing number of slum areas. Hence, the aim of this project is to show solution of housing design that provides better quality of life. The design targets are people who have a lower-middle quality of life or those who are less fortunate, who live in slums. The design methodology within this housing design is a simple survey and unstructured questionnaires, together with literature studies. The design method, on the other hand, is to apply the Greenship home v.1.0 system, featuring green settlement aspects, particularly natural ventilation and lighting, renewable energy, and green open space. The ultimate target is a vertical housing with facilities that support activities of the occupants, having gree open space as well as hard open space for outdoor sport activities, along with renewable system of energy to decrease the emission. Hence, there are solar panels at vertical housing and the multi-purpose building, recycle system of rain water and waste. There are also facilities of un-organic trash to degrade plastic waste and to process it into selling goods that may add the income of occupants. By doing this little thing, people can help save energy, because inorganic waste becomes something useful that can be reused, start using electricity from solar power, and save and be wise in the use of water. Keywords: Outdoor; Renewable Energy; Sustainable; Vertical HousingAbstrakPada dasarnya manusia hidup sekarang dengan bantuan alam dan mahluk hidup lain yang turut menjaga keseimbangan ekologi. Permasalahan yang sedang dihadapi oleh bumi ini, salah satunya ketidakseimbangan ekologi, dimana manusia bertambah namun lahan atau tempat tinggal serta makanannya mengalami penurunan tetap. Salah satu akibatnya adalah banyak berkembangnya permukiman kumuh. Tujuan dari desain ini adalah untuk memperlihatkan solusi merancang permukiman dengan kualitas hidup yang lebih baik daripada permukiman kumuh. Target sasaran desain merupakan masyarakat yang memiliki kualitas hidup menengah ke bawah atau yang kurang mampu, yang berada dipermukiman kumuh. Metodologi yang digunakan dalam perancangan ini adalah survei disertai wawancara secara langsung dan studi literatur. Adapun metode perancangannya sendiri menerapkan sistem Greenship home v.1.0, dengan penekanan pada aspek hunian hijau, khususnya pengudaraan dan pencahayaan alami, energi terbarukan, serta ruang terbuka hijau. Sasaran-akhir perancangan berupa rumah-susun dengan fasilitas yang mendukung kegiatan warga, memiliki ruang terbuka hijau, ruang terbuka dengan perkerasan untuk kegiatan luar-ruang serta energi terbarukan dalam rangka mengurangi emisi. Untuk itu tersedia perangkat panil-surya di bangunan rumah susun dan bangunan serba guna, pada bangunan rumah-susun terdapat fasilitas daur-ulang air hujan dan air limbah. Selain itu tersedia juga fasilitas pengolahan sampah anorganik dalam rangka mengurangi sampah plastik, untuk dijual dan hasilnya menjadi tambahan pendapatan warga. Dengan melakukan hal kecil ini, bisa membantu pengehematan energi, karena sampah anorganik menjadi sesuatu yang berguna yang bisa digunakan kembali, mulai menggunakan listrik yang berasal dari tenaga surya, dan menghemat dan bijak dalam penggunaan air.